이온크로마토그래프를 이용한 조제유류 및 영아용·성장기용 조제식 중 콜린 함량 분석법 연구 - 황경미; 함현숙; 이화정; 강윤정; 윤혜성; 홍진환; 이현영; 김천회; 오금순; Hwang, Kyung Mi; Ham, Hyeon Suk; Lee, Hwa Jung; et al. (Han'gug sigpum wi'saeng anjeonseong haghoeji, 2017)
This study was conducted to establish the analysis method for the contents of choline in infant formulas and follow-up formulas by ion chromatograph (IC). To optimize the method, we compared several conditions for extraction, purification and instrumental measurement using spiked samples and certified reference material (CRM; NIST SRM 1849a) as test materials. IC method for choline was established using Ion Pac CG column and 18 mM $H_2SO_4$ mobile phase. The parameters of validation were specificity, linearity, LOD, LOQ, recovery, accuracy, precision and repeatability. The specificity was confirmed by the retention time and the linearity, $R_2$ was over 0.999 in range of 0.5~10 mg/L. The detection limit and quantification limit were 0.14, 0.43 mg/L. The accuracy and precision of this method using CRM were 95%, 2.1% respectively. Optimized methods were applied in sample analysis to verify the reliability. All the tested products were acceptable contents of choline compared with component specification for nutrition labeling. The standard operating procedures were prepared for choline to provide experimental information and to strengthen the management of nutrient in infant formula and follow-up formula. 본 연구는 "축산물의 가공기준 및 성분규격"에 기준규격은 설정되어 있지 않으나, 국제 기준과의 조화를 위해 콜린의 분석법을 마련하고자 수행하였다. 조제유류에 함유된 콜린 함량 분석을 위해 IC를 이용한 분석법을 확립하고 시중에 유통 중인 제품을 대상으로 적용성을 검토하였다. 콜린 표준품을 이용하여 IC를 이용한 기기분석조건을 확립하고 시료중의 콜린을 추출하여 분석하였다. 분석법 검증은 특이성, 직선성, 검출한계 및 정량한계, 정확성, 정밀성에 대해 수행되었다. 0.5~10 mg/L의 농도범위에서 $R^2=0.999$ 이상의 우수한 직선성을 확인할 수 있었으며, LOD와 LOQ는 각각 0.14, 0.43 mg/L였다. CRM (NIST SRM 1849a) 및 표준물질 첨가법을 이용하여 정확성을 검토하였으며, CRM에서 95%, 조제분유에서 90~91%, 조제우유에서 81~98%의 회수율을 확인할 수 있었다. 정밀성을 검토한 결과 시료 채취량에 따른 반복성은 RSD값이 조제분유 0.4~2.0%, 조제우유 0.5~1.5%, 영아용조제식 0.6~1.0%, 성장기용조제식 0.8~2.7%,로 확인하였으며, 실험일자에 따른 재현성은 조제분유 3.1%, 조제우유 2.5%, 영아용조제식 4.8%, 성장기용조제식 2.7%로 확인하였다. 본 연구에서 확립된 분석법을 적용하여 조제분유 11건, 조제우유 2건, 성장기용조제분유 9건, 영아용조제식 2건, 성장기용조제식 8건 등 국내 유통 중인 조제유류 및 영아용 성장기용조제식 등 32건에 대해 적용성 검토를 실시한 결과 전체 시료에서 분석이 용이하였으며, 모두 표시기준에 적합함을 확인하였다.